2020
DOI: 10.1002/minf.202000113
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Modeling of SARS‐CoV Mpro Inhibitors Identifies Sufugolix, Cenicriviroc, Proglumetacin, and other Drugs as Candidates for Repurposing against SARS‐CoV‐2

Abstract: The main protease (M pro) of the SARS-CoV-2 has been proposed as one of the major drug targets for COVID-19. We have identified the experimental data on the inhibitory activity of compounds tested against the closely related (96 % sequence identity, 100 % active site conservation) M pro of SARS-CoV. We developed QSAR models of these inhibitors and employed these models for virtual screening of all drugs in the DrugBank database. Similarity searching and molecular docking were explored in parallel, but docking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…QSAR models developed by us earlier were used for selection of drugs 40 , 41 that could be repurposed as combinations and exclusion of potential drug-drug interactions and side effects. 36 All models were developed according to the best practices of QSAR modeling, 34 , 42 , 43 with special attention paid for data curation 44 , 45 , 46 and rigorous external validation.…”
Section: Methodsmentioning
confidence: 99%
“…QSAR models developed by us earlier were used for selection of drugs 40 , 41 that could be repurposed as combinations and exclusion of potential drug-drug interactions and side effects. 36 All models were developed according to the best practices of QSAR modeling, 34 , 42 , 43 with special attention paid for data curation 44 , 45 , 46 and rigorous external validation.…”
Section: Methodsmentioning
confidence: 99%
“…NCATS released, via OpenData Portal ( ) the quantitative HTS data on drugs approved for clinical use tested in the SARS-CoV-2 cytopathic effect (CPE) assay. We used the chemical structures and data of 3957 molecules in SMILES format of this SARS-CoV-2 CPE evaluation from the work of Alves et al [ 17 ]. From those 3957 molecules, there are 1401 molecules that were used to build (910 molecules in the training set) and validate (409 and 82 molecules in the test and test 2 sets, respectively) the SARS-CoV-2 QSAR model.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been reported with the development of ligand-based CADD approaches for the discovery of inhibitors against SARS-CoV-2 [ 16 , 17 , 18 ]. Ghosh et al reported the development of several Monte Carlo optimization-based, quantitative structure–activity relationship (QSAR) models with a diverse dataset comprising 88 compounds with SARS-CoV-2 M pro assay from the ChEMBL database and the best model was used for virtual screening of 60 NPs from recent publications [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…From these, five compounds were shown to be inactive in the counter screen indicating that they were true positives in the CPA assay: umifenovir, imatinib, promethazine, fluoxetine, and reserpine. Umifenovir (arbidol) was also identified as active in the QSAR models for severe acute respiratory syndrome coronavirus (SARS-CoV) M pro our group described recently [20].…”
Section: Comparison Of the Drug-target Associations In The Coke Datasmentioning
confidence: 98%